Political use and consequences of sport events - Rybka, Pauline Johanna (2014)
In the theory part of this thesis will examine the connection between politics and sport, including the politicization of major sport events and the particular role of non-democratic states as host nations. In the empirical part, three case studies (Summer Olympics Beijing 2008, Winter Olympics Sochi 2014, and FIFA World Cup Qatar 2018) will be analyzed in the light of how they have influenced (or have the potential to influence) reforms, the adoption of democratic structures, and the human rights situation.